# Miller - Miller Effect MOSFET Define Gi = 1 1 GD = Ri RD vi...

This preview shows pages 1–4. Sign up to view the full content.

Miller Effect - MOSFET Define i i 1 G R = , = D D 1 G R , = g g 1 G R , = ds ds 1 g r in ig s i vv G =+ (1) v gs = v g () ( ) od s D m g g o g d vg G g v v vs C ++ = (2) ( ) = g d g g d m vg G s C vs C g (3) = gd m og ds D gd sC g gGs C (4) + in g g g gs g o gd i v G v sC v v sC (5) g gg g s go g d i 1 v Gv s C s C G ⎡⎤ + + ⎣⎦ (6) gd i g g g gs gd o ii sC 1 vvv 1 Gs C s C v GG + + + ⎢⎥ (7)

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
- 2 - () gd io i g gg sg d i sC vv G v 1 1 G sC sC G + = ⎡⎤ ++ + ⎢⎥ ⎣⎦ (8) gd gd m i o g dDd s d i sC sC g G v sC G g 1 1 G sC sC G + =⋅ + (9) or gd i o i sC G D v U K 1 G + + (10) in which we have defined: =− g dm Ds C g =+ + g s Us C G g + g gs gd KGs Cs C . Next, we get ii o g d o i Gv v sC D v GK U + + (11) or og d oo vsC DD GKU GKU −⋅ = (12) which is gd o sC D D v1 −= (13)
- 3 - The voltage gain is then given by () oi ii gd i vG D1 K U DsC 1 UG K =⋅ + ⎡⎤ ⎢⎥ + ⎣⎦ (14) in terms of the circuit parameters ( ) ( ) ( ) ig dm g d i g gs gd gd D ds gd gd m Gs C g D K U D s C G G sC sC sC G g sC sC g == +− ++ + (15) or ( ) ( ) im g d o i i g gs gd gd D ds gd m gd Gg s C v v G G sC sC sC G g sC g sC =− + + (16) Define ' D

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 8

Miller - Miller Effect MOSFET Define Gi = 1 1 GD = Ri RD vi...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online